(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
In this paper, I present a novel interpretation of the notion ’formative power’ in Kant’s "Critique of the Power of Judgment" (§65). I defend the view that for Kant the formative power is a fundamental, immaterial, intrinsic natural power in the organized being. It is a final cause that generates the purposive form of the materials of an organized being. Reading God’s creation as the primary and nature’s formative power as a secondary final cause of the purposive form of nature allows us to see the consistency of Kant’s theological and philosophical views in the field of biology.